Effectiveness of prehabilitation for patients undergoing orthopaedic surgery: protocol for a systematic review and meta-analysis - Alison B Rushton; Anuj Punnoose; Ori Weiss (BMJ Open)
Introduction Undergoing major surgery can induce physical and functional decline. Prehabilitation programmes aim to improve physical fitness and function preoperatively and could enhance postoperative recovery and outcomes. Prehabilitation interventions have been utilised across a range of orthopaedic populations of all ages and can be multimodal in nature. The aim of this study is to evaluate the effectiveness of prehabilitation for patients undergoing orthopaedic surgery including day surgery procedures. It will also investigate the components of prehabilitation to understand optimum duration and frequency of programmes.Methods/design Systematic review and meta-analysis designed in accordance with PreferredReporting Items for Systematic Review and Meta-Analysis Protocols. A comprehensive electronic search will be performed in MEDLINE, CINAHL, AMED, Embase, PEDro and Cochrane CENTRAL databases in order to identify randomised control trials published between January 2000 to 25 March 2019. ISI Web of Science, System for information on grey literature and the European Union clinical trials registry will identify studies that are underway or unpublished. Two independent reviewers will carry out the searches, study selection (title and abstract and full text stages), data extraction, risk of bias assessment (Cochrane Risk of Bias tool 2.0) and evaluation of overall strength of evidence. Meta-analyses will be used for data which demonstrates homogeneity, otherwise a narrative synthesis will be performed for groups of studies of high heterogeneity (I2 >50%). The overall strength of the body of evidence will be assessed using Grading of Recommendations Assessment, Development and Evaluation.Ethics and dissemination This study raises no ethical issues. This study aims to identify the effectiveness of prehabilitation interventions and may assist clinicians in determining which components, duration, frequency and the method of delivery would form the most effective prehabilitation intervention for patients undergoing an orthopaedic surgical procedure. The findings will be disseminated through publication in a peer-reviewed journal and conference presentations.PROSPERO registration number CRD42019123268.